Evaluation of medical malpractice claims in obstetric ultrasonography: Opinion of The Council of Forensic Medicine in Turkey. (November 2021) - Terece, Cem; Gürpınar, Kağan; Büyükatak, Koray; Atacan, Sibel Çağlar; Ağırbaş, Ajda; Madazlı, Rıza
Abstract: Aim: The Council of Forensic Medicine is an institution affiliated with the Ministry of Justice in the Republic of Turkey which acts in an official oversight capacity in cases of alleged medical malpractice in forensic medical science. Sonographers may face judicial sanctions as a result of ultrasonography examinations that they do not perform according to current guidelines. In this study we focused our attention to claims of medical malpractice related to obstetric ultrasonography that had been referred to the Council of Forensic Medicine. Our aim was to investigate the causes of malpractice claims related to obstetric ultrasonography and to present the expert opinions of our council about these claims in the light of literature. We have also planned to discuss what can be done with current guideline information to prevent situations that cause malpractice claims. Materials and methods: The study herein was performed on 73 claims of medical malpractice in obstetric ultrasonography findings, all of which were referred by forensic authorities to the Second Specialization Board of Council Forensic Medicine from 2014 to 2018. A retrospective review of the reports generated from information contained within case files illuminates the reasoning behind medical error claims. Among the reasons examined are features of the ultrasonographic evaluation (number, week of examination, health institution), the traits of the evaluating physicians (institutions, branches, academic titles), congenital anomalies detected after birth, and maternal age. Results: Analysis of the data shows that 79.5% of ultrasonographic examinations leading to claims of medical malpractice were performed in private health institutions. All cases of medical malpractice claims were associated with undiagnosed congenital anomalies, and that the form for informed consent was obtained for only 19.1% of cases that underwent second level ultrasonographic examination. Further, 53.3% of cases with congenital anomalies subject to litigation were anomalies of the extremities, and all four cases of alleged malpractice within obstetric ultrasonography were associated with extremity anomalies. The variety of academic titles of physicians performing the ultrasonographic examinations was not statistically significant. It was concluded that two ultrasonography examinations performed by two nuclear medicine specialists were not in accordance with medical norms. Conclusion: Although organizations such as AIUM, ACR, and ACOG try to set standards for ultrasound examination through practice guidelines, it is difficult to establish optimal standards for ultrasonographic examination. In light of the guidelines created by the above organizations, each country should set its own standard based on their own socioeconomic and health data. We conclude that it is not appropriate for obstetric ultrasonographic examinations to be performed by specialists in fields such as nuclear medicine, where ultrasonographic examinations are not a part of the core training curriculum. Obtaining a signed informed consent form from the patient prior to the second level ultrasonography examination will be useful for medicolegal defense purposes should a subsequent claim of malpractice be filed. Highlights: Obstetricians and radiologists who perform obstetric ultrasonography are at risk of encountering malpractice claims. Malpractice claims related with obstetric ultrasound are increasing year by year. Obstetric ultrasound examinations may not always be performed in accordance with the guidelines of international organizations. It is not appropriate to perform obstetric USG examination by specialists who do not have obstetric USG training in the core education program.